Komunikasi Pemasaran Global Terpadu: Tantangan di Era Digital - Niko Yehezkiel; Nafiah Ariani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Discovery of computers and specifically the internet, led to fundamental changes in concept, strategy, tactic, and implementation of business, marketing, and marketing communications, which shifted from conventional to modern markets in the digital age. Integrated Marketing Communications (IMC) is a concept derived from the research made by practitioners and academics in anticipating the expiry of old strategies that are no longer reliable. In turn, IMC became a new paradigm to be used as a basic reference in facing challenges in the global market. The application of IMC concepts and strategies to the global market is known as Integrated Global Marketing Communications (IGMC) planning. Changes that occur in consumer behavior, message development patterns, the proliferation of media, especially digital media, and the integration of marketing communication elements are the basis of the IGMC strategic development plan. The implementation of the IGMC program can be expected to be a road map to achieve organizational and corporate success in the digital age. This paper synthesized the viewpoints of different experts and provides the author’s analysis, interpretation, and theorizing.